Does the noise in my head bother you? : a rock 'n' roll memoir - Tyler, Steven, 1948- (Ecco Press, 2011)
The frontman of the classic rock band Aerosmith tells his story, including his rise to rock stardom in the 1970s, the band's drop in popularity, and their comeback in the late 1980s and 1990s.